Economic Geography / Third Edition - Darkenwald Gerald Gordon; Jones Fielden Clarence (The Macmillan Company, 1967)
The Field of Economic Geography, The Occupations of Hunting and Fishing, Forests and the Forest Industries, The Grazing Industries, The Occupation of Farming, The Occupation of Mining, Manufacturing, Transportation Facilities and Trade, Index.